Relevansi dan Kontinuitas Pemikiran Islam Klasik dalam Intelektualisme Islam Melayu Nusantara - Ris'an Rusli; Y. Yanto (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2018)
This study aims to determine the relevance and continuity of classical Islamic thought in Nusantara Malay Islamic intellectualism, expected to be useful in adding to the treasures of the study of history and intellectual thought while also contributing to the preservation of scientific traditions in Indonesia. This study uses a type of qualitative research with a library research model with a historical approach. The data collection techniques in the study are heuristic techniques, verification, interpretation, and historiography. The results of this study conclude that first, the process of the intellectual tradition of Malay Archipelago Islam is inseparable from the process of transmission and diffusion of Islamic teachings and ideas always involving a kind of "intellectual networks", both those formed among ulama and intellectuals as a whole. Second, the relevance of classical Islamic thought in Nusantara Malay Islamic intellectualism can be seen in the existence of the two largest organizations in Indonesia, the Nahdlatul Ulama (NU) whose intellectualism led to the Jabariah sect and Muhammadiyah whose intellectualism was directed towards Muta'zilah. Third, the continuity of classical Islamic thought in Nusantara Malay Islamic intellectualism gave rise to Malay-archipelago modernist thinkers closer to the Mu'tazilah's historical establishment than to the traditionalist historical stance.